Kreativität grenzenlos!?: Inner- und außerschulische Expertisen zu inklusiver Kultureller Bildung - Sauter, Sven; Henning, Ina; Witte, Katharina (transcript, 2019)
Active participation in culture and the arts for everybody - an overview of existing approaches of inclusive cultural education.